Drivers of households’ willingness to generate their electricity post amendment of Electricity Regulation Act in South Africa - Hlungwani, Hlamalani Cordley (University of the Witswatersrand, Johannesburg, 2022)
Purpose: Prior to amendment of Electricity Regulation Act in South Africa, which increased the threshold for embedded generation without licencing 1 Megawatt (MW) to 100 MW, one of the factors that was considered to prevent consumers to generate their own electricity was the licencing requirements challenges. The research investigated other drivers that affect the households’ willingness to generate their own electricity in South Africa, given the recent amendment to the Electricity Regulation Act which has relaxed those licencing requirements. Research design, methodology and approach: The researcher sent questionnaires to various electricity households’ consumers, for which 120 respondents were used as a sample to the study, employing a quantitative methodology. Findings: The study has found that there is a positive relationship between electricity customers willingness to generate own electricity and their environmental concern. The more electricity customers are concerned about the environment the more they will be willing to generate their own electricity. The study also discovered the existence of positive relationship between electricity customers willingness to generate own electricity and the perception of self-effectiveness. The more electricity customers perceive that they are capable of generating their own electricity the more they will be willing to generate their own electricity. Value: The research can be used to assist in understanding the factors that might be preventing households from generating their own electricity despite the removal of the licencing barriers post amended of the Act. It can also be used to identify areas of focus when providing awareness to residential customers on the importance of electricity generation
Thesis presented in partial fulfilment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand
Keywords: UCTD; Perceived benefits; Environmental concern; Perceived self- effectiveness; SDG-7: Affordable and clean energy